2020
DOI: 10.3928/19404921-20190930-02
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Function, Physical Activity, Falls, Medication Use, and Life Satisfaction Among Residents in Assisted Living Settings

Abstract: The purpose of this study was to test for gender differences among assisted living residents. This was a secondary data analysis using data from the first 64 facilities participating in the ongoing Function Focused Care for Assisted Living study using the Evidence Integration Triangle (FFC-AL-EIT). A total of 593 residents were recruited from 64 assisted living settings. Differences by gender with regard to function, physical activity, falls, total numbers of medications, and satisfaction with assisted living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
1
9
2
Order By: Relevance
“…In this study, the number of married male elderly was higher than the female elderly. In addition, this study found that elderly men were more satisfied with their health and overall QOL than were women, which is not consistent with the results of several previous studies that elderly women’s life satisfaction level was higher or not significantly different from men’s [ 27 , 28 ]. The average life expectancy of men and women in Korea in 2018 is 79.7 and 85.7 years, respectively, but the life expectancy excluding the disease period is 64.4 years in both males and females, showing that women live longer than men in unhealthy conditions and alone [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, the number of married male elderly was higher than the female elderly. In addition, this study found that elderly men were more satisfied with their health and overall QOL than were women, which is not consistent with the results of several previous studies that elderly women’s life satisfaction level was higher or not significantly different from men’s [ 27 , 28 ]. The average life expectancy of men and women in Korea in 2018 is 79.7 and 85.7 years, respectively, but the life expectancy excluding the disease period is 64.4 years in both males and females, showing that women live longer than men in unhealthy conditions and alone [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The results of previous studies related to life satisfaction of the elderly have been inconsistent depending on gender. Some studies showed that the level of life satisfaction of older women was higher than that of older men [ 27 , 28 ], while others reported no gender difference in life satisfaction [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting finding of the present study was that the variables age and sex showed small, and in some cases, non-significant, levels of correlation with the other variables. These results were not in agreement with previous studies; in general, age and sex are considered to influence the levels of PA [ 58 , 59 ], PF [ 60 , 61 ], and body weight [ 14 , 62 ] and, in turn, affect HRQoL levels [ 39 , 40 ].…”
Section: Discussioncontrasting
confidence: 89%
“…Furthermore, participant gender and age group were associated with these motor aptitude outcomes, regardless of the presence or absence of PD. Older women were more likely to have motor impairment in GMA and Coordinative motor aptitude, corroborating data from previous studies (Coelho-Junior et al, 2021;Oliveira et al, 2019) that have suggested both biologically based differences related to brain architecture and functioning, hormonal variables, and environmentally based differences related to lifestyle and social roles (Marrocco & McEwen, 2016;Resnick et al, 2020).…”
Section: Discussionsupporting
confidence: 87%